Khalwat as a Therapy in Improving Mental Health, as an Effort to Overcome Drug Abuse - Putri, Melyza Eka; As-Shidqi, Muhammad Haikal; Febriyani, Rina (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Abstract: The development of the times in the current era can be said to be very fast. Any technology can be created by humans themselves. Various problems also arise between humans with one another with various different causes. This will cause a disturbance in human health, especially mental health disorders. Mental health is a very important thing for the human body, because it is one of the most important parts in living life and also balance. When a person's mental health is not balanced they will try to do negative things, especially using drugs, which is considered to be calming. Therefore, a person needs therapy to be able to help maintain mental health. There are many ways to do mental health therapy. One of them is with seclusion. Seclusion is withdrawing from the crowd and solitude to get closer to Allah swt. Seclusion is done with different time spans. The method used in this paper is a qualitative method, and the technique used is a literature study technique, namely data collection by reviewing the literature and collecting books, written materials and references relevant to the research being conducted.